Between the queen and the cabby Olympe de Gouges's Rights of woman - Cole, John R. (John Richard), 1941- (McGill-Queen's studies in the history of ideas ;, 2011)
"Students of the French Revolution and of women's right are generally familiar with Olympe de Gouges's bold adaptation of the Declaration of the Rights of Man and of the Citizen. However, her Rights of Woman has usually been extracted from its literary context and studied without proper attention to the political consequences of 1791. In Between the Queen and the Cabby, John Cole provides the first full translation of de Gouges's Rights of Woman and the first systematic commentary on its declaration, its attempt to envision a non-marital partnership agreement, and its support for persons of colour. Cole compares and contrasts de Gouges's two texts, explaining how the original text was both her model and her foil. By adding a proposed marriage contract to her pamphlet, she sought to turn the ideas of the French Revolution into a concrete way of life for women. Further examination of her work as a playwright suggests that she supported equality not only for women but for slaves as well. Cole highlights the historical context of de Gouges's writing, going beyond the inherent sexism and misogyny of the time in exploring why her work did not receive the reaction or achieve the influential status she had hoped for. Read in isolation in the gender-conscious twenty-first century, de Gouges's Rights of Woman may seem ordinary. However, none of her contemporaries, neither the Marquis de Condorcet nor Mary Wollstonecraft, published more widely on current affairs, so boldly attempted to extend democratic principles to women, or so clearly related the public and private spheres. Read in light of her eventual condemnation by the Revolutionary Tribunal, her words become tragically foresighted: "Woman has the right to mount the Scaffold; she must also have that of mounting the Rostrum."--Publisher's website.